Physico-Chemical Characteristics Of Pinang River Estuary, Balik Pulau, Penang - Rosli, Nurul Ruhayu Mohd (2018)
The Pinang River is located at the north-western of Penang Island. Its length is approximately 6.5 km, with narrow and shallow upstream, but wider and deeper downstream. This river supplies freshwater to nearly one-third of Balik Pulau population. Unfortunately, anthropogenic effluent from agriculture, domestic and aquaculture are being directly discharge into the river thus, deteriorating the water quality. Therefore, this study was undertaken to determine the Pinang River estuarine processes which involve the mixing of freshwater and seawater that may influence the river hydrodynamic, biological, physical and chemical aspects. These characteristics would possibly affect the estuarine water circulation, river transport time scales (i.e. residence time and flushing time) and pollutants (i.e. nutrient and sediment concentrations; and its loadings). Net ecosystem metabolism (NEM) status in Pinang River was also evaluated in terms of ratio between photosynthesis and respiration. Diurnal studies were carried out for 24 hours at two stations during two tidal cycles at spring and neap tides and wet and dry season. A secondary data (from October 2007 until October 2008) on river discharge, salinity and volume along Pinang River were utilised to determine the residence time and flushing time. Pinang River estuarine system was considered as micro-tidal and partially stratified estuary. The flushing time did not influence the residence time (R2=0.028) in Pinang River.